Effect of COVID-19 on Clinical Spectrum of patients presenting to the Dermatology Outpatient Department of a Tertiary Care Hospital in Rawalpindi - Shawana Sharif ,Muhammad Amer Saleem ,Nauman Nisar ,Abdul Quddus Butt (Journal of Rawalpindi Medical College, 2020)
Introduction: COVID-19 has significantly decreased the influx of patients presenting with dermatologic diseases at hospitals due to lockdown and restrictions pertaining to stop the spread of COVID-19. Objective: To describe the effect of changes of COVID-19 on the clinical spectrum of patients presenting in dermatology OPD at a tertiary care unit in Rawalpindi, Pakistan. Method: A comparison of the census of the dermatology outpatient department of three corresponding months before and after COVID-19 was done. During the pandemic year (2020) a significant decrease in patients visiting the dermatology outpatient department was observed. Results: This reduction was much more prominent for the extreme of ages i.e. children and elderly. Infections and infestations were the predominant causes of presentation of patients at our dermatology outpatient department in pre-COVID-19 as well as during the pandemic. Patients with serious dermatologic conditions (e.g., pemphigus vulgaris, erythroderma, and cellulitis), however, had significantly fewer visits during the pandemic as compared to Pre COVID-19 era. In contrast, patients suffering from eczema constituted a significantly higher rate of outpatient visits during the pandemic. Conclusion: Patients with serious dermatologic conditions (e.g., pemphigus vulgaris, erythroderma, and cellulitis), had significantly fewer visits during the pandemic as compared to the Pre COVID-19 era. In contrast, patients suffering from eczema constituted a significantly higher rate of outpatient visits during the pandemic.